Far Haven [videorecording (DVD)] - Shockley, William, 1963-; Rikert, Dustin, 1974-; Gire, Tom, 1968-; Chase, Bailey, 1972-; Boxleitner, Bruce; Righetti, Amanda, 1983-; Kove, Martin; Martinez, A., 1948- (Imagicomm Entertainment, 2024)
In 1887, Hunter Braddock moves back to Far Haven, Arizona, to start over with his two young children, but when his father-in-law is brutally attacked, he must take on the corrupt forces strangling the town in order to protect what he loves most.